Peran Media Massa Barat Membingkai Aksi Terorisme - Shepriyani Miftajanna (Jurnal Komunikasi, 2022)
The 9/11 terrorism attack has become one of the issues covered specifically by the media. Terrorism stereotypes are closely related to Islam due to the prominence of news broadcast by the media. The media have a role in influencing public perceptions. Agenda setting and framing theory can explain that mass media has the ability to transfer two elements, namely awareness and information to the public agenda and its attention to issues that are only considered important by the mass media. The intensity of news about terrorism is broadcast more than in other spheres and the framing of terrorism is related to Islamic groups, thus affecting people's perceptions of labeling acts of terrorism that are identical to Islam. As well as using the functions of the media agenda, public agenda and policy agenda to analyze the role of the media in reviewing terrorism